Phenylephrine to Treat Hypoxemia during One-Lung Ventilation in a Pediatric Patient - Schloss, Brian; Martin, David; Beebe, Allan; Klamar, Jan; Tobias, Joseph D. (The Thoracic and Cardiovascular Surgeon Reports, 2013)
To improve surgical visualization and facilitate the procedure, one-lung ventilation (OLV) is frequently used during thoracic surgery. Although generally well tolerated, the ventilation–perfusion inequality induced by OLV may lead to a decrease in oxygenation and, at times, hypoxemia. Effective treatment algorithms and strategies are necessary for the treatment of hypoxemia during OLV to ensure that the technique can be continued without interruption and allow for completion of the surgical procedure. Treatment strategies may include applying positive end expiratory pressure to the nonoperative lung, continuous positive airway pressure or low flow oxygen insufflation to the operative lung, decreasing anesthetic agents that interfere with hypoxic pulmonary vasoconstriction (HPV), or switching to total intravenous anesthesia. Although less commonly employed, α-adrenergic agonists may also improve oxygenation during OLV by augmenting HPV. We present a 12-year-old girl who developed hypoxemia during OLV, which was not corrected by the usual maneuvers. Hypoxemia was successfully treated with a phenylephrine infusion. The potential applications of α-adrenergic agonists such as phenylephrine in the treatment of hypoxemia during OLV are discussed and its physiologic basis reviewed.
Keywords: pediatric; hypoxia; one-lung ventilation